An assessment of the parrot trade on Obi Island (Northern Moluccas, Indonesia) reveals heavy exploitation of the vulnerable Chattering Lory (Lorius garrulus) - H Eden W Cottee-Jones; John C Mittermeier; Endang Christine Purba; N Maulidina Ashuri; Eka Hesdianti (KUKILA, 2014)
Trapping for the domestic and international pet trade is a significant conservation threat to several species of psittacines in the Northern Moluccas, Indonesia. Field studies conducted on the status of parrots in this region in the early 1990s assessed the impact of the trade and provided recommendations for regulations, but since then little research has been conducted to update the conservation status of these species. In July–August 2012, we conducted interviews and field surveys to assess the status of the parrot trade in seven villages on Obi Island, Maluku Utara province. We found substantial variation in prices depending on their final market, a heterogeneous pattern of trapping rates around the island, and that parrot trapping is very rarely the primary source of income for the trapper. Here we estimate the annual harvest for the three most commonly trapped species: Chattering Lory Lorius garrulus, Violet-necked Lory Eos squamata, and Eclectus Parrot Eclectus roratus. Our estimate for the minimum annual harvest of the Vulnerable-listed Chattering Lory on Obi is substantially higher than previous estimates for the global annual harvest of this species. It seems likely that the Chattering Lory, and in particular the distinctive flavopalliatus subspecies, is more threatened than is currently assumed. We recommend urgent action to assess the population size of this species on Obi, and suggest that a scheme of stakeholder-led no-take zones may be an effective conservation strategy for parrots on the island.